2021
DOI: 10.1002/jcb.30175
|View full text |Cite
|
Sign up to set email alerts
|

PAK1 and PAK2 in cell metabolism regulation

Abstract: P21-activated kinases (PAKs) regulate processes associated with cytoskeletal rearrangements, such as cell division, adhesion, and migration. The possible regulatory role of PAKs in cell metabolism has not been well explored, but increasing evidence suggests that a cell metabolic phenotype is related to cell interactions with the microenvironment. We analyzed the impact of PAK inhibition by small molecule inhibitors, small interfering RNA, or gene knockout on the rates of mitochondrial respiration and aerobic g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…4D and fig. S17), which was found to be among the most highly expressed genes in the 3q29Del interval in nearly all mouse and human cell types and was recently shown to be involved in cellular energy metabolism ( 22 ). We found that P21 (RAC1) Activated Kinase 2 (PAK2) is one of the seven 3q29-encoded proteins identified in a proximity labeling protein-protein interaction mitochondria map ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…4D and fig. S17), which was found to be among the most highly expressed genes in the 3q29Del interval in nearly all mouse and human cell types and was recently shown to be involved in cellular energy metabolism ( 22 ). We found that P21 (RAC1) Activated Kinase 2 (PAK2) is one of the seven 3q29-encoded proteins identified in a proximity labeling protein-protein interaction mitochondria map ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…P21-activated kinase (PAK) plays a crucial role in regulating a wide range of processes associated with cytoskeletal rearrangement, including cell migration, apoptosis, and cell division (34). P21activated kinase 2 belongs to the PAK family of serine/threonine kinases and functions as a downstream substrate of Rho family GTPases, including Rac and CDC42 (35).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was found that PAK1-deficient β-cells had decreased mitochondrial copy number, mitochondrial respiration, disrupted redox balance, elevated ROS, diminished levels of the mitochondrial electron transport chain complex proteins and increased apoptosis [ 6 ]. In addition, PAK inhibition by IPA3 in leukemia cell lines significantly lowered OCR, revealing roles for PAK1 and PAK2 in the metabolic regulation of both mitochondrial respiration and aerobic glycolysis [ 40 ]. Moreover, a recent report indicated that PAK2 stimulates the activity of the cancer-specific isoform of pyruvate kinase which directs the cell metabolism to aerobic glycolysis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%